Sharing the happiness of receiving APC - Siti Nur Azwin, Zulkapri (2020)
Kuantan, 28 August 2020 – The recipient of the Anugerah Perkhidmatan Cemerlang (APC), Samini Mat Hassan who is a Vehicle Driver at the Centre for Property Management and Development (PPPH), Universiti Malaysia Pahang (UMP) considers the award he received as a special gift in conjunction with his retirement on 21st June 2020 ago.